On the α/Fe Bimodality of the M31 Disks - Chiaki Kobayashi; Souradeep Bhattacharya; Magda Arnaboldi; Ortwin Gerhard (The Astrophysical Journal Letters, 2023)
An outstanding question is whether the α /Fe bimodality exists in disk galaxies other than in the Milky Way. Here we present a bimodality using our state-of-the-art galactic chemical evolution models that can explain various observations in the Andromeda galaxy (M31) disks, namely, elemental abundances both of planetary nebulae and of red giant branch stars recently observed with the James Webb Space Telescope. We find that in M31 a high- α thicker-disk population out to 30 kpc formed by a more intense initial starburst than that in the Milky Way. We also find a young low- α thin disk within 14 kpc, which is formed by a secondary star formation M31 underwent about 2–4.5 Gyr ago, probably triggered by a wet merger. In the outer disk, however, the planetary nebula observations indicate a slightly higher- α young (∼2.5 Gyr) population at a given metallicity, possibly formed by secondary star formation from almost pristine gas. Therefore, an α /Fe bimodality is seen in the inner disk (≲14 kpc), while only a slight α /Fe offset of the young population is seen in the outer disk (≳18 kpc). The appearance of the α /Fe bimodality depends on the merging history at various galactocentric radii, and wide-field multiobject spectroscopy is required for unveiling the history of M31.